Legal Framework for Regulation of Income Tax on Cryptocurrency Transactions Based on the Principle of Justice: Comparative Legal Study with Canada - Ariska Cesar Divian Candra KUSUMA; Tunggul Anshari Setia NEGARA; Riana SUSMAYANTI (International Journal of Environmental, Sustainability, and Social Science, 2022)
The Regulation of the Minister of Finance of the Republic of Indonesia Number 68/PMK.03/2022 as the legal basis for cryptocurrency income tax does not reflect the principle of fairness because the consideration is based on the principle of ease of administration. This paper aims to provide an alternative income tax legal framework on cryptocurrency based on the principle of justice. It is expected to be a step to increase state revenue through the sector of cryptocurrency tax. This paper employs a conceptual and comparative approach to normative research. Furthermore, the researcher compares income tax regulations and policies on cryptocurrency in Indonesia and Canada with the theory of justice to obtain answers to legal problems. The Regulation of the Minister of Finance of the Republic of Indonesia Number 68/PMK.03/2022 does not reflect the principle of justice because the final tax rate does not reflect the tax burden. In addition, there are limitations on the tax collector's authority, so tax collection is not comprehensive. Therefore, this paper compares and analyses income tax regulations and policies in Indonesia and Canada to obtain several alternative forms of fair tax legal framework on cryptocurrency. Alternative cryptocurrency income tax regulation that can be accommodated by the government is to change to a progressive rate to fulfill tax fairness, change the collection system to a self-assessment and do not differentiate the source of income and also cooperate with various exchanges to exchange transaction data to prevent criminal acts.